Economía verde: efecto del gasto público ambiental en el desempeño económico verde desde el año 2013 al año 2016 - Flor Cajilema, Karen Emilia (2018)
The objective of the present research consists in discerning the existence of a correlation between two elements directly related to the green economy being environmental public spending and the ‘green’ economic performance as reflected in the Global Green Economy Index from the years 2014 and 2016 respectively. In order to achieve the objective proposed, a quantitative method was established based on various selection criteria necessary for undergoing a comparative study of relevant cases. This last premise was based on two source with the first indicator focusing on public environmental expenditures obtained from the OECD, and the second from country’s overall Global Green Econmy Index ratings from 2014 and 2016, respectively. The contribution of this analysis is intended to highlight and understand the role of the state in the implementation of a green economy, given the growing importance of the topic in recent years. The results obtained are feasible for the posterior development of research on the relationship among public spending, sustainable development and environmental Keynesianism.